2008
DOI: 10.1371/journal.pone.0001746
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of the FTO Gene with Obesity in Children of Caucasian and African Ancestry Reveals a Common Tagging SNP

Abstract: Recently an association was demonstrated between the single nucleotide polymorphism (SNP), rs9939609, within the FTO locus and obesity as a consequence of a genome wide association (GWA) study of type 2 diabetes in adults. We examined the effects of two perfect surrogates for this SNP plus 11 other SNPs at this locus with respect to our childhood obesity cohort, consisting of both Caucasians and African Americans (AA). Utilizing data from our ongoing GWA study in our cohort of 418 Caucasian obese children (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
188
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(207 citation statements)
references
References 50 publications
15
188
2
2
Order By: Relevance
“…The fat mass and obesity-associated gene (FTO) was recently identified as an obesity candidate gene by three largescale and independent genome-wide association studies, which strongly associated several single nucleotide polymorphisms (SNPs) of FTO with obesity-related traits, including body mass index, hip circumference and body weight. 1 --3 Significant associations between FTO and obesity were independently replicated in many other studies of different populations, including Korean, 4 Japanese, 5 Malay, 6 Chinese, 6,7 Belgian, 8 British, 9,10 Dutch, 11,12 German, 13 Finnish, 14 French, 15 Swedish, 16,17 Caucasian, 18 African 19 and American. 18,20 --22 In mice, FTO deficiency caused postnatal growth retardation and a significant reduction in adipose tissue and lean body mass, 23 and FTO deletion resulted in lesser postnatal growth and lower serum IGF-1 levels.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The fat mass and obesity-associated gene (FTO) was recently identified as an obesity candidate gene by three largescale and independent genome-wide association studies, which strongly associated several single nucleotide polymorphisms (SNPs) of FTO with obesity-related traits, including body mass index, hip circumference and body weight. 1 --3 Significant associations between FTO and obesity were independently replicated in many other studies of different populations, including Korean, 4 Japanese, 5 Malay, 6 Chinese, 6,7 Belgian, 8 British, 9,10 Dutch, 11,12 German, 13 Finnish, 14 French, 15 Swedish, 16,17 Caucasian, 18 African 19 and American. 18,20 --22 In mice, FTO deficiency caused postnatal growth retardation and a significant reduction in adipose tissue and lean body mass, 23 and FTO deletion resulted in lesser postnatal growth and lower serum IGF-1 levels.…”
Section: Introductionmentioning
confidence: 80%
“…Several SNPs in intron 1 of chicken FTO (especially rs9939609) showed credible associations with obesity, similar to findings in various human populations. 7,17,18 In the pig, FTO SNPs are also related to intramuscular fat content and growth rate traits. 27,28 The associations of FTO SNPs with body weight, body composition and fatness traits in chickens supports the functional importance of FTO in birds, similar to that in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A cluster of variants in the first intron of FTO show strong and highly significant association with obesity and obesity-related traits in three independent genome-wide association studies, [3][4][5] findings that have been replicated in several other studies. [15][16][17][18] In the present study, we identified three novel SNPs in the fourth intron, which are not in linkage disequilibrium with SNPs in the first intron, and examined the association between c.896 þ 223A4G and obesity as well as related phenotypes. Our study shows no increased risk of obesity for the novel variant and no significant differences in BMI or BMI SDS according to genotype among normal weight adolescents or among children and adolescents with severe FTO variants and insulin action in obese children and adolescents JA Jacobsson et al obesity.…”
Section: Discussionmentioning
confidence: 99%
“…26 The SNP is reported to have a high minor allele frequency in Caucasians (∼0.4) but very low in Asian population (∼0.1), whereas its association with obesity and type II diabetes has been confirmed in many populations but not in Chinese Han subjects. 11,[18][19][20][21][22][23][24][25][26][34][35][36][37][38] The six GWAS SNPs were found to be associated with type II diabetes and have been replicated for Chinese and Japanese populations only for association with type II diabetes. [27][28][29] However, these SNPs have not been previously studied with respect to obesity, and the Pakistani population represents an interesting ethnic group because of the many cultural and social restrictions and with an increasing rate of obesity and type II diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The association of common FTO variants, especially rs9939609, with obesity has been confirmed in Caucasians; however, the results in Asian populations are conflicting. [16][17][18][19][20][21][22][23][24][25] In Pakistan, there is limited research in the field of obesity genetics. A recent study in the Pakistani population indicated the association of this SNP with obesity in women and proposed that the SNP may play its role by affecting plasma glucose and leptin levels.…”
Section: Introductionmentioning
confidence: 99%